Prevalence and treatment of psychiatric disorders other than psychosis in children and adolescents with 22q11DS: Examining associations with social and role functioning. (August 2017) - Armando, Marco; Lin, Ashleigh; Pontillo, Maria; Vicari, Stefano
Abstract: Individuals with chromosome 22q11 deletion syndrome (22q11DS) have high rates of psychotic disorders. Less is known about their psychopathology and how it is treated prior to the peak period of risk for psychotic disorder. There is also a lack of evidence on how functioning is impacted by psychopathology in this population. The aim of this study was to investigate the prevalence and treatment of non-psychotic psychiatric disorders, and how these factors are associated with psychosocial functioning in children and adolescents with 22q11DS. 126 individuals with 22q11DS aged 8–17 participated in the study. Participants were assessed for psychiatric diagnoses, social and role functioning, anxiety and depressive symptoms and IQ. Information on current treatments was collected. 52.4% of the sample presented with at least one psychiatric disorder. Mood and anxiety disorders were the most frequent, followed by behavioural disorder. Individuals with a psychiatric disorder had significantly lower general, role and social functioning. Only 27% of participants with a psychiatric diagnosis were receiving any mental health treatment at the time of assessment. Findings suggest the high prevalence of psychiatric disorders in youth with 22q11DS, which significantly impacts psychosocial functioning. Despite this, psychiatric disorders tend to remain untreated in this population. Highlights: More than half of the sample presented with at least one psychiatric disorder. Individuals with a psychiatric disorder had lower general, role and social functioning independently from the IQ level. Only 27% of participants with a psychiatric diagnosis were receiving any mental health treatment.